High-performance dielectric materials and their preparation methods suitable for ultra-thin layer high-capacity MLCCs
By using BaTiO3 matrix material with a particle size of 60-150nm and chemical coat doping, a high-performance dielectric material was prepared, which solved the problem that existing dielectric materials were difficult to meet ultra-thin layering and high reliability in small size and high capacity MLCC, and achieved the effect of maintaining excellent dielectric performance at a lower sintering temperature.
Patent Information
- Application Number
- CN202411951401.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
Existing dielectric materials are difficult to meet the needs of ultra-thin layering and high reliability in small size and high capacity MLCC, and the sintering temperature is high and the overall dielectric performance is insufficient.
BaTiO3 with a particle size of 60-150nm is used as the matrix material, and the coating material BaO-MgO-SiO2-R2O3-MnO2-V2O5 is doped by chemical coating technology to prepare a high-performance dielectric material, with reduced sintering temperature and excellent dielectric performance.
It realizes the preparation of ultra-thin layer, large-capacity MLCC dielectric materials at low sintering temperatures, maintains excellent dielectric properties, and is suitable for the design and application of small-size and high-capacity MLCC.
Smart Images

Figure CN119751051A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of capacitor dielectric materials, and in particular, relates to a high-performance dielectric material suitable for ultra-thin layer large-capacity MLCC and a preparation method thereof. Background Art
[0002] Multilayer ceramic capacitors (MLCC) are widely used in electronic information fields such as mobile communication equipment, base stations, artificial intelligence (AI), new energy vehicles, and supercomputers. With the continuous evolution of science and technology, electronic information technology is increasingly moving towards integration, miniaturization, and intelligence. As a key passive component to ensure the stable operation of electronic circuits, MLCC is used the most in the board and occupies the largest area (more than 50%). Therefore, miniaturization, thin layers, high capacity, and high reliability have become its main development trends.
[0003] At present, the average grain size of barium titanate-based dielectric materials for small-sized, high-capacity MLCCs widely used on the market is usually greater than or equal to 150nm, and the dielectric layer thickness of MLCCs is more than 1μm. In order to match the preparation of smaller-sized, larger-capacity MLCCs, the dielectric layer thickness needs to be reduced to 0.3-0.8μm, so dielectric materials with smaller particle sizes and higher performance are needed to ensure the performance and reliability of thin-layer MLCCs. In addition, the existing dielectric materials have a high sintering temperature, and the comprehensive dielectric properties cannot meet the requirements of ultra-thin-layer, large-capacity MLCCs. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a high-performance dielectric material suitable for ultra-thin layer large-capacity MLCC and a preparation method thereof. The high-performance dielectric material of the present invention adopts BaTiO3 with a particle size of 60-150nm synthesized by solid phase method as the base material and is prepared by chemical coating technology, which can meet the needs of ultra-thin layer MLCC dielectric materials, and at the same time meet the requirements of being prepared at a lower sintering temperature and a reducing atmosphere, and can further improve the problem of co-firing with nickel metal inner electrodes, thereby meeting the requirements of base metal inner electrode (nickel inner electrode) multilayer ceramic capacitors that are widely used now.
[0005] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0006] On one hand, the present invention provides a high-performance dielectric material, the composition expression of the dielectric material is BaTiO3-BaO-MgO-SiO2-R2O3-MnO2-V2O5, wherein BaTiO3 is a matrix, and BaO-MgO-SiO2-R2O3-MnO2-V2O5 is a doping coating material; the molar contents of the matrix and the doping coating material are as follows: BaTiO3 100mol%, BaO 0.3-2mol%, MgO 0.2-2mol%, SiO2 0.3-2mol%, R2O3 0.1-1mol%, MnO2 0.1-1mol%, V2O5 0-2mol%; wherein R2O3 is represented by a rare earth element oxide, which is at least one of Y2O3, Ho2O3, Dy2O3, and Yb2O3; and the particle size of the BaTiO3 matrix is 60-150nm.
[0007] Another aspect of the present invention provides a method for preparing a high-performance dielectric material, which comprises the following steps:
[0008] (1) BaTiO3 powder is mixed with a dispersion medium, and after ball milling and dispersion, a BaTiO3 matrix suspension is obtained;
[0009] (2) dissolving the soluble metal salt of the coating element in deionized water according to the molar fraction to obtain a coating element metal salt solution;
[0010] (3) adding the coating element metal salt solution and silica sol dropwise to the BaTiO3 matrix suspension obtained in step (1), stirring and mixing evenly to obtain a preliminary slurry;
[0011] (4) adjusting the pH of the preliminary slurry to 6-10, allowing the coated elements to gradually precipitate, and aging for 1-2 hours to obtain a suspension of dielectric material particles with a uniform surface coating;
[0012] (5) drying and calcining the dielectric material particle suspension to obtain dielectric material particles;
[0013] (6) Adding a binder to the dielectric material particles to form granules, then pressing and molding, and then debinding and sintering to obtain the high-performance dielectric material.
[0014] Furthermore, the preparation process of the silica sol is: silicon alkoxide is uniformly mixed with ethanol, acetic acid and deionized water in a certain volume ratio to obtain the silica sol.
[0015] Furthermore, in step (4), aqueous ammonia is used to adjust the pH of the preliminary slurry.
[0016] Furthermore, in step (5), the drying temperature is 80-120° C., the calcination temperature is 300-600° C., and the calcination time is 2-8 h.
[0017] Furthermore, in step (6), the binder is PVA, and the amount of the binder is 8-20 wt.%.
[0018] Furthermore, in step (6), the compression molding process is: under a pressure of 2-6 MPa, the medium material particles are pressed into a sheet material with a diameter of 10 mm using an axial tablet press.
[0019] Furthermore, the process conditions for debinding are: heating to 300-500°C at a heating rate of 3-5°C / min and keeping the temperature for 4-6h.
[0020] Furthermore, in step (6), the sintering is divided into two stages: reducing atmosphere sintering and reoxidation sintering; the conditions for reducing atmosphere sintering are: heating to 1120-1180°C at a heating rate of 10-100°C / min and keeping the temperature for 1-3h, and the oxygen partial pressure in this stage is 10 -6 ~10 -9 atm; the reoxidation sintering conditions are: cooling to 800-1000℃ at a cooling rate of 5-20℃ / min and keeping warm for 3-8h. The oxygen partial pressure in this stage is 10 -3 ~10 -5 atm.
[0021] The present invention also provides application of the high-performance dielectric material in ultra-thin layer large-capacity MLCC.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention adopts 60-150nm BaTiO3 (BT) powder synthesized by solid phase method as matrix material, and performs doping and coating modification by BaO-MgO-SiO2-R2O3-MnO2-V2O5. The sintering temperature of the obtained dielectric material is significantly reduced while maintaining excellent dielectric properties. The dielectric material can be applied to the preparation of ultra-thin layer and large-capacity MLCC.
[0024] The present invention prepares dielectric materials by selecting BaTiO3 powder with a grain size less than 150nm and doping and modifying it with optimized components. The preparation of BT with fine grain size can meet the application requirements of ultra-thin layer MLCC. The smaller grain size can prepare an ultra-thin dielectric layer with a thickness of 0.3-0.8μm while ensuring that the single layer of dielectric material is not less than 5 grains; at the same time, the thinner dielectric layer thickness can make the MLCC design with more stacking numbers without changing the total volume. Therefore, the dielectric material of the present invention can ensure the dielectric constant while being more conducive to the design and application of small-size, high-capacity MLCCs; the dielectric material of the present invention modified by optimized component doping and coating can meet the requirements of reducing atmosphere sintering in the range of 1120-1180°C, while achieving a higher room temperature dielectric constant and better resistivity, which is conducive to co-firing with nickel metal inner electrodes during the preparation of MLCC, and can solve the problems of fracture and oxidation caused by the mismatch of sintering shrinkage rate between the nickel metal inner electrode and the ceramic dielectric material at high temperature (greater than 1150°C), thereby ensuring the capacity and reliability of the MLCC and being conducive to ensuring the consistency and integrity of the MLCC structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM image of the BT matrix powder in Example 2 of the present invention.
[0026] Figure 2 This is a TEM image of the dielectric material after chemical coating in Example 2 of the present invention.
[0027] Figure 3 This is a SEM image of the sintered ceramic disc of Example 2 of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The invention provides a high-performance dielectric material. The composition expression of the dielectric material is BaTiO3-BaO-MgO-SiO2-R2O3-MnO2-V2O5, wherein BaTiO3 is a matrix, and BaO-MgO-SiO2-R2O3-MnO2-V2O5 is a doping coating material; the molar contents of the matrix and the doping coating material are as follows: BaTiO3 100mol%, BaO 0.3-2mol%, MgO 0.2-2mol%, SiO2 0.3-2mol%, R2O3 0.1-1mol%, MnO2 0.1-1mol%, V2O5 0-2mol%; wherein R2O3 is a rare earth element oxide, which is at least one of Y2O3, Ho2O3, Dy2O3 and Yb2O3; and the particle size of the BaTiO3 matrix is 60-150nm.
[0030] The method for preparing the high-performance dielectric material comprises the following steps:
[0031] (1) BaTiO3 powder is mixed with a dispersion medium, and after ball milling and dispersion, a BaTiO3 matrix suspension is obtained;
[0032] (2) dissolving the soluble metal salt of the coating element in deionized water according to the molar fraction to obtain a coating element metal salt solution;
[0033] (3) adding the coating element metal salt solution and silica sol dropwise to the BaTiO3 matrix suspension obtained in step (1), stirring and mixing uniformly to obtain a preliminary slurry; the preparation process of silica sol is: mixing silicon alkoxide with ethanol, acetic acid and deionized water in a certain volume ratio to obtain silica sol;
[0034] (4) adjusting the pH of the preliminary slurry to 6-10 with ammonia water to gradually precipitate the coating elements, aging for 1-2 hours, and obtaining a suspension of dielectric material particles with a uniform surface coating;
[0035] (5) drying and calcining the dielectric material particle suspension to obtain dielectric material particles; wherein the drying temperature is 80-120° C., the calcining temperature is 300-600° C., and the calcining time is 2-8 hours;
[0036] (6) Adding a binder to the dielectric material particles to form granules, and then pressing and molding, and then debinding and sintering to obtain the high-performance dielectric material; wherein the binder is PVA, and the amount of the binder is 8-20wt.%; the pressing process is: under a pressure of 2-6Mpa, using an axial tablet press to press the dielectric material particles into a sheet material with a diameter of 10mm. The process conditions for debinding are: heating to 300-500℃ at a heating rate of 3-5℃ / min and keeping warm for 4-6h; sintering is divided into two stages: reducing atmosphere sintering and reoxidation sintering; the conditions for reducing atmosphere sintering are: heating to 1120-1180℃ at a heating rate of 10-100℃ / min and keeping warm for 1-3h, and the oxygen partial pressure in this stage is 10 -6 ~10 -9 atm; the reoxidation sintering conditions are: cooling to 800-1000℃ at a cooling rate of 5-20℃ / min and keeping warm for 3-8h. The oxygen partial pressure in this stage is 10 -3 ~10 -5 atm.
[0037] The present invention also provides application of the high-performance dielectric material in ultra-thin layer large-capacity MLCC.
[0038] The present invention will be further described below by means of specific examples.
[0039] Example 1
[0040] The composition expression of the dielectric material of this embodiment 1 is:
[0041] 100mol%BaTiO3-0.8mol%MgO-1mol%MnO2-1mol%BaO-1mol%SiO2-0.8mol%Y2O3.
[0042] The method for preparing the high-performance dielectric material of the first embodiment comprises the following steps:
[0043] (1) 150 nm BaTiO3 powder is mixed with isopropanol as a dispersion medium, and after ball milling and dispersion, a BaTiO3 matrix suspension is obtained;
[0044] (2) dissolving soluble metal salts of coating elements Mg, Mn, Ba, and Y in deionized water according to their molar fractions to obtain coating element metal salt solutions; mixing SiO2 alkoxide with ethanol, acetic acid, and deionized water in a certain volume ratio to obtain silica sol;
[0045] (3) adding the coating element metal salt solution and silica sol dropwise to the BaTiO3 matrix suspension obtained in step (1), stirring and mixing uniformly to obtain a preliminary slurry; the preparation process of silica sol is: mixing silicon alkoxide with ethanol, acetic acid and deionized water in a certain volume ratio to obtain silica sol;
[0046] (4) adjusting the pH of the preliminary slurry to 7 with ammonia water to gradually precipitate the coating elements, aging for 2 hours, and obtaining a suspension of dielectric material particles with a uniform surface coating;
[0047] (5) drying the dielectric material particle suspension at 80° C. for 10 h, and then calcining at 500° C. for 3 h to obtain BT-based dielectric material particles with uniform surface coating;
[0048] (6) The dielectric material particles were added with 8 wt % PVA to form pellets, and then pressed into discs with a diameter of 10 mm. The pellets were first heated to 500° C. at a heating rate of 5° C. / min and kept at that temperature for 4 h for debinding. The pellets were then heated to 1140° C. at a heating rate of 30° C. / min and kept at that temperature for 1 h for sintering. During the sintering process, the oxygen partial pressure was kept at 10 -8 atm; then the temperature was lowered to 1000°C at 10°C / min and kept at this temperature for 4 hours for reoxidation. The oxygen partial pressure was kept at 10 -3 atm, BT-based dielectric materials can be obtained.
[0049] The BT-based dielectric material was double-sided polished with 2000-grit sandpaper, and then silver electrodes were evenly applied on both sides, and then the electrical performance was tested. The room temperature resistance was tested using an Agilent Technologies, 4339B high resistance meter, and the relationship between the dielectric constant and temperature and the relationship between the capacitance and temperature were tested using an Agilent Technologies, 4980A; the room temperature capacitance and loss were tested using an Agilent Technologies, 4294A precision impedance analyzer, and the room temperature dielectric constant was calculated using the following calculation method:
[0050]
[0051] Where C is the room temperature capacitance, ε0 is the vacuum dielectric constant, d is the thickness of the ceramic sample, and S is the electrode area of the ceramic sample.
[0052] The room temperature dielectric constant of the BT-based dielectric material of the first embodiment can reach 2510, the room temperature dielectric loss is 1.4%, and the room temperature resistivity is 3.5=10 12Ω·cm, the average grain size after sintering is about 170nm, which is suitable for the dielectric layer material of multilayer ceramic capacitors with a dielectric layer thickness of 0.8μm. Its capacitance changes less than ±15% in the temperature range of -55 to 85℃, meeting the performance of X5R type MLCC dielectric materials.
[0053] Example 2
[0054] The composition expression of the dielectric material of this embodiment 2 is:
[0055] 100mol%BaTiO3-0.3mol%MgO-0.2mol%MnO2-0.8mol%BaO-0.8mol%SiO2-0.4mol%V2O5-0.5mol%Dy2O3.
[0056] The method for preparing the high-performance dielectric material of the second embodiment comprises the following steps:
[0057] (1) 120 nm BaTiO3 powder was mixed with isopropanol as a dispersion medium, and after ball milling and dispersion, a BaTiO3 matrix suspension was obtained;
[0058] (2) dissolving soluble metal salts of coating elements Mg, Mn, Ba, V, and Dy in deionized water according to their molar fractions to obtain coating element metal salt solutions; mixing SiO2 alkoxide with ethanol, acetic acid, and deionized water in a certain volume ratio to obtain silica sol;
[0059] (3) adding the coating element metal salt solution and silica sol dropwise to the BaTiO3 matrix suspension obtained in step (1), stirring and mixing uniformly to obtain a preliminary slurry; the preparation process of silica sol is: mixing silicon alkoxide with ethanol, acetic acid and deionized water in a certain volume ratio to obtain silica sol;
[0060] (4) adjusting the pH of the preliminary slurry to 7 with ammonia water to gradually precipitate the coating elements, aging for 2 hours, and obtaining a suspension of dielectric material particles with a uniform surface coating;
[0061] (5) drying the dielectric material particle suspension at 80° C. for 10 h, and then calcining at 500° C. for 3 h to obtain BT-based dielectric material particles with uniform surface coating;
[0062] (6) The dielectric material particles were added with 8 wt % PVA to form pellets, and then pressed into discs with a diameter of 10 mm. The pellets were first heated to 500° C. at a heating rate of 5° C. / min and kept at that temperature for 4 h for debinding. The pellets were then heated to 1130° C. at a heating rate of 30° C. / min and kept at that temperature for 1 h for sintering. The oxygen partial pressure was kept at 10 -8atm; then the temperature was lowered to 950°C at 10°C / min and kept at this temperature for 4 hours for reoxidation. The oxygen partial pressure was kept at 10 -3 atm, BT-based dielectric materials can be obtained.
[0063] The SEM image of the BT matrix powder in Example 2 is as follows Figure 1 As shown; the TEM image of the dielectric material after chemical coating in Example 2 is as follows Figure 2 As shown; the SEM image of the sintered ceramic disc is as follows Figure 3 shown.
[0064] The electrical properties of the dielectric material of Example 2 were tested according to the dielectric properties testing method shown in Example 1.
[0065] Example 3
[0066] The composition expression of the dielectric material of this embodiment 3 is:
[0067] 100mol%BaTiO3-0.5mol%MgO-0.6mol%MnO2-0.8mol%BaO-0.8mol%SiO2-0.8mol%Y2O3-0.6mol%Ho2O3.
[0068] The method for preparing the high-performance dielectric material of the embodiment 3 comprises the following steps:
[0069] (1) 80 nm BaTiO3 powder was mixed with isopropanol as a dispersion medium, and after ball milling and dispersion, a BaTiO3 matrix suspension was obtained;
[0070] (2) dissolving soluble metal salts of coating elements Mg, Mn, Ba, Y, and Ho in deionized water according to their molar fractions to obtain coating element metal salt solutions; mixing SiO2 alkoxide with ethanol, acetic acid, and deionized water in a certain volume ratio to obtain silica sol;
[0071] (3) adding the coating element metal salt solution and silica sol dropwise to the BaTiO3 matrix suspension obtained in step (1), stirring and mixing uniformly to obtain a preliminary slurry; the preparation process of silica sol is: mixing silicon alkoxide with ethanol, acetic acid and deionized water in a certain volume ratio to obtain silica sol;
[0072] (4) adjusting the pH of the preliminary slurry to 7 with ammonia water to gradually precipitate the coating elements, aging for 2 hours, and obtaining a suspension of dielectric material particles with a uniform surface coating;
[0073] (5) drying the dielectric material particle suspension at 80° C. for 10 h, and then calcining at 500° C. for 3 h to obtain BT-based dielectric material particles with uniform surface coating;
[0074] (6) The dielectric material particles were added with 8 wt % PVA to form pellets, and then pressed into discs with a diameter of 10 mm. The pellets were first heated to 500° C. at a heating rate of 5° C. / min and kept at that temperature for 4 h for debinding. The pellets were then heated to 1130° C. at a heating rate of 30° C. / min and kept at that temperature for 1 h for sintering. The oxygen partial pressure was kept at 10 -8 atm; then the temperature was lowered to 950°C at 10°C / min and kept at this temperature for 4 hours for reoxidation. The oxygen partial pressure was kept at 10 -3 atm, a BT-based dielectric material can be obtained. The dielectric material of Example 3 is tested for electrical properties according to the dielectric property test method shown in Example 1.
[0075] Comparative Example 1
[0076] The composition expression of the dielectric material of Comparative Example 1 is:
[0077] 100mol%BaTiO3-0.8mol%MgO-1mol%MnO2-1mol%BaO-1mol%SiO2-0.8mol%Y2O3.
[0078] The preparation method of the dielectric material of Comparative Example 1 is:
[0079] BaTiO3 powder was used as the matrix powder, and the dielectric material was prepared by solid phase doping method. First, the dopant oxide and BaTiO3 powder were mixed according to the stoichiometric ratio, ground and dispersed using zirconium beads with a diameter of 3 mm, and wet ball milled with ethanol for 12 hours at a speed of 350 rpm.
[0080] After ball milling, the material was dried in an oven at 120°C for 12 hours to obtain a dry dielectric material powder. The dielectric material powder was ground and sieved with a 200-mesh screen, and then 10 wt% of PVA was added as a binder to granulate the material and press it into a disc with a diameter of 10 mm. The material was heated to 500°C at a heating rate of 5°C / min and kept warm for 4 hours for debinding; then the material was heated to 1150°C at a heating rate of 30°C / min and kept warm for 1 hour for sintering. The oxygen partial pressure was kept at 10 -8 atm; then the temperature was lowered to 950°C at 10°C / min and kept at this temperature for 4 hours for reoxidation. The oxygen partial pressure was kept at 10 - 3 atm, a BT-based dielectric material can be obtained. The dielectric material of Comparative Example 1 is tested for electrical properties according to the dielectric property test method shown in Example 1.
[0081] Comparative Example 2
[0082] The composition expression of the dielectric material of Comparative Example 2 is:
[0083] 100mol%BaTiO3-0.3mol%MgO-0.2mol%MnO2-0.8mol%BaO-0.8mol%SiO2-0.4mol%V2O5-0.5mol%Dy2O3.
[0084] The preparation method of the dielectric material of Comparative Example 2 is:
[0085] BaTiO3 powder was used as the matrix powder, and the dielectric material was prepared by solid phase doping method. First, the dopant oxide and BaTiO3 powder were mixed according to the stoichiometric ratio, ground and dispersed using zirconium beads with a diameter of 3 mm, and wet ball milled with ethanol for 12 hours at a speed of 350 rpm.
[0086] After ball milling, the material was dried in an oven at 120°C for 12 hours to obtain a dry dielectric material powder. The dielectric material powder was ground and sieved with a 200-mesh screen, and then 10 wt% of PVA was added as a binder to granulate and pressed into a 10 mm diameter disc. The temperature was first raised to 500°C at a heating rate of 5°C / min and kept for 4 hours for debinding; then the temperature was raised to 1140°C at a heating rate of 30°C / min and kept for 1 hour for sintering. The oxygen partial pressure was kept at 10 during the sintering process. -8 atm; then the temperature was lowered to 1000°C at 10°C / min and kept at this temperature for 4 hours for reoxidation. The oxygen partial pressure was kept at 10 - 3 atm, a BT-based dielectric material can be obtained. The dielectric material of Comparative Example 2 is tested for electrical properties according to the dielectric property test method shown in Example 1.
[0087] Comparative Example 3
[0088] The composition expression of the dielectric material of Comparative Example 3 is:
[0089] 100mol%BaTiO3-0.5mol%MgO-0.6mol%MnO2-0.8mol%BaO-0.8mol%SiO2-0.8mol%Y2O3-0.6mol%Ho2O3.
[0090] The preparation method of the dielectric material of Comparative Example 3 is carried out according to the steps of Comparative Example 2. The dielectric property test method shown in Example 1 is used to test the electrical properties of the dielectric material of Comparative Example 3.
[0091] The performance test results of the dielectric materials of various embodiments and comparative examples are shown in Table 1.
[0092] Table 1 Dielectric material performance test results
[0093]
[0094]
[0095] It can be seen from Table 1 that the dielectric material of the embodiment of the present invention has a higher room temperature dielectric constant, lower dielectric loss, better resistivity and smaller grain size, and the capacitance changes little in the temperature range of -55 to 85°C, which can meet the requirements of ultra-thin layer MLCC dielectric materials.
[0096] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any modifications or equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A high-performance dielectric material, characterized in that: The composition expression of the dielectric material is BaTiO3-BaO-MgO-SiO2-R2O3-MnO2-V2O5, wherein BaTiO3 is a matrix and BaO-MgO-SiO2-R2O3-MnO2-V2O5 is a doping coating material; the molar contents of the matrix and the doping coating material are as follows: BaTiO3 100mol%, BaO 0.3-2mol%, MgO 0.2-2mol%, SiO2 0.3-2mol%, R2O3 0.1-1mol%, MnO2 0.1-1mol%, V2O5 0-2mol%; wherein R2O3 is represented by a rare earth element oxide, which is at least one of Y2O3, Ho2O3, Dy2O3 and Yb2O3; and the particle size of the BaTiO3 matrix is 60-150nm.
2. A method for preparing the high-performance dielectric material according to claim 1, characterized in that: The steps include: (1) BaTiO3 powder is mixed with a dispersion medium, and after ball milling and dispersion, a BaTiO3 matrix suspension is obtained; (2) dissolving the soluble metal salt of the coating element in deionized water according to the molar fraction to obtain a coating element metal salt solution; (3) adding the coating element metal salt solution and silica sol dropwise to the BaTiO3 matrix suspension obtained in step (1), stirring and mixing evenly to obtain a preliminary slurry; (4) adjusting the pH of the preliminary slurry to 6-10, allowing the coated elements to gradually precipitate, and aging for 1-2 hours to obtain a suspension of dielectric material particles with a uniform surface coating; (5) drying and calcining the dielectric material particle suspension to obtain dielectric material particles; (6) Adding a binder to the dielectric material particles to form granules, then pressing and molding, and then debinding and sintering to obtain the high-performance dielectric material.
3. The method for preparing a high-performance dielectric material according to claim 2, characterized in that: The preparation process of the silica sol is as follows: silicon alkoxide is uniformly mixed with ethanol, acetic acid and deionized water in a certain volume ratio to obtain the silica sol.
4. The method for preparing a high-performance dielectric material according to claim 2, characterized in that: In step (4), the pH of the preliminary slurry is adjusted using aqueous ammonia.
5. The method for preparing a high-performance dielectric material according to claim 2, characterized in that: The drying temperature in step (5) is 80-120° C., the calcination temperature is 300-600° C., and the calcination time is 2-8 hours.
6. The method for preparing a high-performance dielectric material according to claim 2, characterized in that: In step (6), the binder is PVA, and the amount of the binder is 8-20wt.%.
7. The method for preparing a high-performance dielectric material according to claim 2, characterized in that: The compression molding process is: under the condition of a pressure of 2-6Mpa, the medium material particles are pressed into a sheet material with a diameter of 10mm using an axial tablet press.
8. The method for preparing a high-performance dielectric material according to claim 2, characterized in that: The process conditions for debinding are: heating to 300-500℃ at a heating rate of 3-5℃ / min and keeping warm for 4-6h.
9. The method for preparing a high-performance dielectric material according to claim 2, characterized in that: In step (6), the sintering is divided into two stages: reducing atmosphere sintering and reoxidation sintering; the conditions for reducing atmosphere sintering are: heating to 1120-1180°C at a heating rate of 10-100°C / min and keeping the temperature for 1-3h, and the oxygen partial pressure in this stage is 10 -6 ~10 -9 atm; the reoxidation sintering conditions are: cooling to 800-1000℃ at a cooling rate of 5-20℃ / min and keeping warm for 3-8h. The oxygen partial pressure in this stage is 10 -3 ~10 -5 atm.
10. Application of the high-performance dielectric material according to claim 1 in ultra-thin layer large-capacity MLCC.